The dynamics of coordination patterns in multiteam systems response to emergency: Case study from a pharmaceutical enterprise - Zhang, Ya-Wei; Shah, Wasi Ul Hassan; Xiao, Yu-Chun; Shafait, Zahid (Frontiers in Psychology, 2022)
Dynamic forces of multiteam systems (MTS) can increase system uncertainty, and effective coordination can compensate for destructive forces brought by MTS dynamics. However, it is unclear how MTS adapt their coordination pattern to dynamic forces. This study based on division of labor theory; examined how MTSs responded to an emergency production incident in Zhejiang Huisong Pharmaceutical Company in China during the COVID-19 pandemic through a qualitative and quantitative study. We found that the fluidity of system structural configuration has an important impact on the coordination pattern adjustments in a crisis. Specifically, when the leadership team has high (low) centrality in the MTS structure, centralized (decentralized) coordination patterns enhance MTS performance. Our results help managers to consider the differences in coordination patterns in crisis management in ways that assist them in adapting an effective coordination pattern to changing and uncertain operational conditions.